Synthesis and Characterization of a Novel Nonlinear Optical Material Mg2Na2ZnB4O10. (2016) - Dagdale, Shivaji R.; Muley, Gajanan G.
Abstract: A novel borate compound with the chemical formula Mg2 Na2 ZnB4 O10 (MNZB) has been synthesized first time from the 2MgO- Na2 O-ZnO-2B2 O3 system via solid-state reaction. The obtained polycrystalline borate material MNZB was characterized by powder X-ray diffraction, Fourier transform infrared (FT-IR) spectroscopy, and second harmonic generation (SHG) measurement. Ultraviolet-visible spectroscopy has been carried out to analyze transmission of the MNZB crystals grown by slow cooling method. The optical band gap has been estimated. The functional groups were identified by using the FT-IR data. The SHG efficiency of the crystal was obtained by the Kurtz powder technique and it is found to be 2.78 times that of potassium dihydrogen phosphate. The results are presented and discussed.